2D and 3D lanthanide metal–organic frameworks constructed from three benzenedicarboxylate ligands: synthesis, structure and luminescent properties. Issue 5 (10th January 2018) - You, Li-Xin; Zhao, Bai-Bei; Liu, Hui-Jie; Wang, Shu-Ju; Xiong, Gang; He, Yong-Ke; Ding, Fu; Joos, Jonas J.; Smet, Philippe F.; Sun, Ya-Guang
Abstract : Nineteen Ln-MOFs with four different crystal structures were prepared and the luminescence was studied. Abstract : Nineteen lanthanide–benzenedicarboxylate complexes were obtained under similar hydrothermal conditions: [Ln(IP-Py)(HIP-Py)(H2 O)2 ] n (Ln = Pr (1 ), Sm (2 ), Eu (3 ), Gd (4 ), Tb (5 ), Dy (6 )), [Ln4 (IP)6 (H2 O)4 (DMF)·DMF· m H2 O] n (Ln = Sm, m = 1 (7 ), Eu, m = 1.5 (8 ), Gd, m = 1.5 (9 ), Tb, m = 1.5 (10 ), Dy, m = 1 (11 ), Ho, m = 1.5 (12 )), [Ln2 (IP-Py)2 (IP)(H2 O)4 ·H2 O] n (Ln = Sm (13 ), Eu (14 ), Tb (15 ), Dy (16 )) and [Ln2 (IP-Py)2 (TP)(H2 O)4 ·H2 O] n (Ln = Sm (17 ), Eu (18 ), Gd (19 )), where: H2 IP-Py = 5-(4-pyridyl)-isophthalic acid), H2 IP = isophthalic acid, H2 TP = terephthalic acid. Complexes1–6 exhibit a two-dimensional layered structure based on H2 IP-Py. For7–12, the Ln 3+ ions are linked into one-dimensional chains with two triple-stranded helices of opposite handedness and further constructed into a two-dimensional layer by coordination of the IP 2− ligands. For complexes13–16 and17–19, a similar two-dimensional layer was formed by coordination of Ln 3+ and IP-Py 2−, and three-dimensional pillar-layered frameworks were formed due to the layers bridged by the auxiliary IP 2− or TP 2− ligand, respectively. Most complexes show the characteristic narrow-banded lanthanide 4f N –4f N emission in combination with luminescence from the ligands, with the relative contribution depending on the energy transfer from the ligands to the lanthanides. The ligands play an important role in the sensitization of the lanthanide emission. The onset of the main excitation band for the Eu 3+ complexes is found at the lowest energy for14, enabling excitation by near-UV LEDs. The complexes containing the technologically relevant ions for (back) lighting applications, Tb 3+ (green) and Eu 3+ (red), are evaluated in detail in terms of luminescence lifetime and thermal stability. The emission intensity of selected Eu 3+ and Tb 3+ compounds is stable up to room temperature.